2021
DOI: 10.1002/er.6530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cooling system integrated with different phase change material s and its effect on peak load shaving

Abstract: Summary In this study, a vapor‐compression cooling system utilizing different phase change materials (PCMs) has been studied whereby the electricity consumption peak load is shifted. More specifically, the dynamic performance of cooling systems with and without using PCM is evaluated for the hottest day of the year. The proposed system uses the cooling energy to freeze, or “discharge” the PCM during nighttime when the cooling load is minimally needed and uses the stored thermal energy during the peak load hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…9 The energy storage characteristics make microencapsulated PCM the material of choice in various sectors such as textiles, 10 construction and buildings, 11 thermal storage 12 and cold energy storage. 13 The polymer shell material for microencapsulation can be polymethyl methacrylate, 14 polystyrene, 15 melamine-formaldehyde, 16 a biodegradable polymer such as gum arabic 17 etc. The porous structure of the foam has been demonstrated in several studies to be a cause of PCM leakage, which is a crucial disadvantage of PU foam integrated PCM composite material.…”
Section: Introductionmentioning
confidence: 99%
“…9 The energy storage characteristics make microencapsulated PCM the material of choice in various sectors such as textiles, 10 construction and buildings, 11 thermal storage 12 and cold energy storage. 13 The polymer shell material for microencapsulation can be polymethyl methacrylate, 14 polystyrene, 15 melamine-formaldehyde, 16 a biodegradable polymer such as gum arabic 17 etc. The porous structure of the foam has been demonstrated in several studies to be a cause of PCM leakage, which is a crucial disadvantage of PU foam integrated PCM composite material.…”
Section: Introductionmentioning
confidence: 99%
“…These facile use characteristics of these materials have attracted interest from numerous sectors, such as solar energy, 16,17 energy-saving building, 18,19 thermoregulated textiles, 20 thermal storage, 21,22 and cold energy storage. 23 The polymeric shell materials comprise polymethyl methacrylate, 13 polystyrene, 24 ureaformaldehyde, 25 melamine-formaldehyde, 26,27 and biodegradable polymers such as Gum Arabic, 28 and so on. MF polymer shell is used in several research studies because of its thermochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation can be achieved using various methods, including physical and chemical processes such as spray drying, 9 fluidized bed, 10 coacervation, 11 emulsion polymerization, 12 suspension polymerization, 13 in‐situ polymerization, 14 and interfacial polymerization, 15 respectively. These facile use characteristics of these materials have attracted interest from numerous sectors, such as solar energy, 16,17 energy‐saving building, 18,19 thermoregulated textiles, 20 thermal storage, 21,22 and cold energy storage 23 . The polymeric shell materials comprise polymethyl methacrylate, 13 polystyrene, 24 urea‐formaldehyde, 25 melamine‐formaldehyde, 26,27 and biodegradable polymers such as Gum Arabic, 28 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Latent heat thermal energy storage (LHTES) is capable of storing and releasing enormous thermal energy, based on the phase transition of employed phase change materials (PCMs). [1][2][3] It is increasingly believed that LHTES can be an effective alternative to address the mismatch between energy supply and demand in time and space dimensions and can practically eliminate the existing energy crisis and atmospheric pollution, when applied in extensive occasions, such as solar thermal utilization, waste heat recovery, building energy saving, electronic device cooling, etc. [4][5][6][7] The charging and discharging performances of LHTES have been evaluated in feasible literatures and it is found that the thermal performance of LHTES is inseparable from thermophysical properties of PCMs.…”
Section: Introductionmentioning
confidence: 99%